Improving functional capacity in haemophilia through adapted physical activity: a pilot study protocol - Giuseppe Barone; Erika Pinelli; Laura Bragonzoni; Maria Scoppolini Massini; Raffaele Zinno; Lelia Valdrè; Lydia Piscitelli; Giulio Senesi; Valentina Guarino; Isabella Diletta Cavalieri; Maria Grazia Benedetti; Giuseppina Mariagrazia Farella (BMJ Open Sport & Exercise Medicine)
Haemophilia, a genetic disorder characterised by deficient clotting factors, often leads to musculoskeletal complications such as haemophilic arthropathy. These complications result in reduced functional capacity, muscle weakness and kinesiophobia, which further exacerbate physical inactivity and psychological distress. The World Federation of Haemophilia recommends including regular physical activity in the management plans for individuals with haemophilia, emphasising its benefits for bone and muscle strengthening, improved coordination, maintenance of healthy body weight and enhanced self-esteem.This study aims to evaluate the effectiveness of an adapted physical activity (APA) programme in individuals with haemophilia. The primary objective is to analyse changes in functional capacity following participants’ completion of the exercise programme. Additionally, the study evaluates the programme’s impact on joint mobility, kinesiophobia, limitations in daily activities and static and dynamic balance. It is hypothesised that the APA programme may improve or maintain joint mobility, increase muscle strength, enhance proprioception and reduce fear of movement (kinesiophobia), thus contributing to an overall improvement in physical function in participants.The intervention is carefully designed to prioritise safety and proper execution. It incorporates low-impact, low- to moderate-intensity exercises tailored to individual joint functionality. Supervised by qualified professionals, the programme aims to minimise excessive joint loading and prevent haemarthrosis while promoting muscle strength, joint mobility and proprioception. The programme is structured into 1-hour sessions held twice weekly for 6 months. Each session has three sections: warm-up, the main part (strength, mobility, proprioception and balance exercises) and cool-down.